Palladium adsorbent with fluorescence indication function as well as preparation method and application thereof

The fluorescent porous polymer TMTNO prepared by Schiff base coupling reaction solves the problems of harsh conditions and lack of monitoring functions of existing palladium ion recovery materials, and achieves efficient palladium ion recovery and real-time fluorescence indication.

CN119455911APending Publication Date: 2025-02-18ANHUI NORMAL UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411655132.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing porous organic polymer materials used for palladium ion recovery have problems such as harsh synthetic conditions, the use of precious metal catalysts, the time-consuming, difficult to prepare in large quantities, and the lack of effective monitoring functions.

Method used

The Schiff base coupling reaction of hydrazide compounds and aldehyde compounds in a mixed solution of acid and water was prepared to produce a rod-shaped fluorescent porous polymer TMTNO that does not require an organic solvent. This material has a fluorescence indication function and is used for palladium ions. Efficient recycling.

Benefits of technology

It realizes the rapid preparation of high-efficiency palladium adsorbents at room temperature, has high capacity adsorption performance and real-time fluorescence indication function, and is suitable for selective recovery and monitoring of palladium ions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455911A_ABST
    Figure CN119455911A_ABST
Patent Text Reader

Abstract

According to the palladium adsorbent with the fluorescence indication function and the preparation method and application of the palladium adsorbent, an aldehyde compound is dispersed in a mixed solution of acid and water, a turbid liquid of a hydrazide compound and water is dropwise added into the obtained aldehyde compound turbid liquid, stirring reaction is conducted at the room temperature, and the palladium adsorbent with the fluorescence indication function is obtained. Different from a conventional two-step method in which an organic polymer needs to be synthesized firstly, the preparation method disclosed by the invention adopts a strategy of pre-activating an aldehyde monomer by using an acid catalyst, so that the nucleophilicity of an amino monomer is prevented from being reduced, the generation of a semi-amine aldehyde intermediate is accelerated, and the reaction efficiency is improved, so that Schiff base condensation can be rapidly synthesized in a water phase at room temperature, and precious metal catalysis is not needed; and batch production can be realized more easily. And the material has an optical indication performance while having an adsorption capacity on palladium, and can be recycled and reused after elution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of material preparation, and specifically relates to a palladium adsorbent with a fluorescent indication function and a preparation method and application thereof. Background Art

[0002] As a precious metal, palladium is an indispensable key material in the fields of fuel cells, electronics industry, automobile industry and aerospace materials, and its demand has been growing year by year. However, palladium resources are relatively scarce, so the recycling and reuse of palladium metal is of great significance. The existing methods for recovering palladium ions from solutions mainly include precipitation, solvent extraction and activated carbon adsorption. Considering that recyclable palladium ion resources generally exist in low concentrations, the first two are difficult to apply in practice. The activated carbon adsorption method has poor selectivity and is easily interfered. Therefore, the development of a new type of palladium ion capture adsorbent is of great significance for the recovery of palladium resources.

[0003] Porous organic polymers (POPs) are organic polymer porous materials based on light element (C, B, H, O, N) building blocks assembled through strong covalent bonds, with large surface area, high porosity, low density, adjustable chemical structure and excellent physical and chemical stability. The unique structural characteristics make POPs show great potential in the selective separation and recovery of palladium ions.

[0004] In 2020, Professor Ma Shengqian prepared a porous organic polymer containing pyridine under the action of palladium catalyst, which was successfully used in Pd 2+ However, the existing reported POPs materials for palladium ion recovery still have the following shortcomings. They mainly include the following aspects: harsh synthesis conditions, use of precious metal catalysts, long time consumption, and difficulty in large-scale preparation. In addition, they have a single recovery function, making it difficult to effectively monitor the recovery of palladium ions.

[0005] Therefore, it is necessary to prepare a palladium adsorbent with integrated recovery / indication through a simple method. Summary of the invention

[0006] The object of the present invention is to provide a palladium adsorbent with a fluorescent indication function and a preparation method thereof, wherein a hydrazide compound is used as a raw material, and reacts with an aldehyde compound to prepare a fluorescent porous polymer TMTNO with a rod-like structure, and the reaction process does not require an organic solvent, and only requires a simple pre-treatment to successfully prepare the material at room temperature in about ten minutes. The prepared material is rod-shaped when observed under a scanning electron microscope, and is rich in N and O elements, and the raw materials used are easy to obtain, the conditions are simple, and no noble metal catalyst is required. The preparation method is simple, low-cost, and it is easy to achieve the preparation of fluorescent porous organic polymers, and can be prepared in large quantities and stably.

[0007] Another object of the present invention is to provide an application of a palladium adsorbent with a fluorescent indication function, which is used for adsorbing and recovering palladium and can also be used for monitoring the adsorption and recovery of palladium.

[0008] The specific technical solutions of the present invention are as follows:

[0009] A method for preparing a palladium adsorbent with a fluorescent indication function, specifically comprising:

[0010] The aldehyde compound is dispersed in a mixed solution of acid and water, and a suspension of hydrazide compound and water is added dropwise to the obtained suspension of the aldehyde compound, and the mixture is stirred at room temperature to react, thereby obtaining a palladium adsorbent with a fluorescent indication function.

[0011] The molar ratio of the hydrazide compound to the aldehyde compound in the suspension of the hydrazide compound and water is 2:3.

[0012] The dripping is dropwise addition;

[0013] The concentration of the hydrazide compound in the suspension of the hydrazide compound and water is 0.03-0.05 mol / L, preferably 0.04 mol / L;

[0014] The volume ratio of acid to water in the aldehyde compound suspension is 1:1-1.5;

[0015] The dosage ratio of the aldehyde compound to the mixed solution of acid and water in the aldehyde compound suspension is 0.04-0.07 mol / L; preferably: 0.06 mol / L;

[0016] The acid is glacial acetic acid;

[0017] The hydrazide compound is selected from 1,3,5-benzenetricarboxylic acid hydrazide;

[0018] The aldehyde compound is selected from 4,4-biphenyldicarboxaldehyde;

[0019] The water used in the present invention is laboratory deionized water;

[0020] The room temperature stirring reaction refers to the reaction at 20-30° C. for 5-20 min. In order to improve the preparation rate and fluorescence performance of the fluorescent porous organic polymer, preferably, the reaction is carried out at 25° C. for 10 min. The room temperature stirring reaction can be carried out in an oil bath set at 20-30° C.

[0021] After stirring the reaction at room temperature, the crude product is collected, washed, purified, and vacuum dried to obtain a rod-shaped fluorescent porous organic polymer rich in N and O, which is a palladium adsorbent with a fluorescent indication function.

[0022] Preferably, the preparation method of the palladium adsorbent with fluorescent indication function is specifically as follows: 1,3,5-benzenetricarboxylic acid hydrazide is dispersed in deionized water and ultrasonically subjected to 30 minutes; 4,4-biphenyldicarboxaldehyde is dispersed in a mixed solution of glacial acetic acid and deionized water and ultrasonically subjected to 30 minutes, and then the dispersed 1,3,5-benzenetricarboxylic acid hydrazide suspension is dripped into the 4,4-biphenyldicarboxylic acid suspension drop by drop with a dropper, the reaction bottle is placed in a 25°C oil bath pot to react for 10 minutes to obtain a product, the product is filtered and collected, washed with water and tetrahydrofuran for 3-5 times successively, possible unreacted monomers are extracted with tetrahydrofuran Soxhlet for 24 hours, the product is dried in a 60°C vacuum drying oven for 24 hours, and stored at room temperature for standby use.

[0023] More preferably, the preparation method of the palladium adsorbent with fluorescent indication function is as follows: 63 mg of 4,4-biphenyldicarboxaldehyde is dispersed in a mixed solution of 5 mL of glacial acetic acid and deionized water (the volume ratio of glacial acetic acid to deionized water is 1:1), and ultrasonically treated for 30 minutes to obtain a 4,4-biphenyldicarboxaldehyde suspension; 50 mg of 1,3,5-benzenetricarboxylic acid hydrazide is dispersed in 5 mL of deionized water and ultrasonically treated for 30 minutes, and the dispersed 1,3,5-benzenetricarboxylic acid hydrazide suspension is gradually added with a dropper. Drop into the 4,4-biphenyl dicarboxaldehyde suspension, place the reaction bottle in a 25℃ oil bath to react for 10 minutes, activate 4,4-biphenyl dicarboxaldehyde under the action of glacial acetic acid, react with 1,3,5-benzenetricarboxylic acid hydrazide to generate a fluorescent porous organic polymer by Schiff base reaction, collect the product by filtration, wash with water and tetrahydrofuran 3-5 times, extract the possible unreacted monomer with tetrahydrofuran Soxhlet for 24 hours, dry the product in a 60℃ vacuum drying oven for 24 hours, store at room temperature for standby use. Preparation under this condition is conducive to improving the preparation rate of fluorescent porous organic polymers and improving fluorescence properties.

[0024] The present invention synthesizes a fluorescent porous organic polymer by a one-pot Schiff base coupling reaction. The prepared porous polymer introduces a large number of functional groups containing heteroatoms, such as N and O atoms, which can react with Pd 2+ The fluorescent porous organic polymer prepared by the method of the present invention is suitable for optical indication and Pd 2+ of recycling.

[0025] The present invention provides a palladium adsorbent with a fluorescent indication function, which is prepared by the above-mentioned preparation method.

[0026] The palladium adsorbent with fluorescent indication function is in the shape of a rod, with a thickness of 150-250 nm;

[0027] The specific surface area of ​​the palladium adsorbent with fluorescent indication function is 48.3530 m2 / g, and the average pore diameter is 11.5728 nm.

[0028] The palladium adsorbent with fluorescent indication function has the structural formula:

[0029]

[0030] The invention provides a palladium adsorbent with a fluorescent indication function, which is used for adsorbing and recovering palladium. 2+ Adsorption capacity up to 1433.5 mg g -1 ; It can also be used to monitor the adsorption and recovery of palladium, which emits bright blue fluorescence in water. Fig.12 There is a visual legend in the 2+ As the concentration increases, its fluorescence will gradually quench, and it has the function of indicating the palladium recovery process in real time.

[0031] After the palladium adsorbent with fluorescent indication function adsorbs palladium, it is eluted with thiourea aqueous solution and dilute nitric acid aqueous solution, dried and reused. Specifically, in a 0.1M thiourea and 0.1M nitric acid mixed aqueous solution, ultrasonicated for 30 minutes, and used four times within the maximum adsorption range, the Pd 2+ The removal rate can still reach more than 90%.

[0032] The inventors have found that materials rich in nitrogen and oxygen heteroatoms have good affinity for palladium ions. Schiff base reaction is a commonly used and effective method for synthesizing imine compounds, which has the advantage of mild reaction conditions. It not only has the potential for easily preparing porous organic polymers, but also can endow materials with rich nitrogen heteroatoms. Fluorescent signals are suitable as indicator signals for monitoring adsorption processes due to their advantages such as high sensitivity, high resolution, and real-time dynamic observation. Therefore, the present invention has important significance for the efficient separation and recovery of palladium ions by simply preparing porous organic polymers with fluorescent indication functions through Schiff base reaction.

[0033] The palladium adsorbent with fluorescent indication function prepared by the present invention is a palladium ion adsorption material, which can effectively recover Pd contained in the aqueous solution as an adsorbent. 2+ The hydrazide building blocks rich in N and O elements can provide a large number of active sites for the reaction with Pd 2+ And due to the high specific surface area and a large number of binding sites of the porous organic polymer material, it is easy to enrich the target so that the adsorption capacity is higher, and after the adsorption is completed, the Pd element attached to the material is eluted, and the experimental material can be repeatedly used. At the same time, as a fluorescent porous organic polymer, it emits bright blue fluorescence in water, Fig.12 Visual legend, and as Pd 2+As the concentration increases, its fluorescence will gradually quench, and it has the function of indicating the palladium recovery process in real time.

[0034] The invention uses common commercially available chemical reagents as monomer raw materials and is prepared by Schiff base reaction. The raw materials are simple and low in cost. The prepared rod-shaped fluorescent porous organic polymer rich in nitrogen and oxygen elements has an optimal fluorescence excitation wavelength of 365nm and a maximum emission wavelength of 470nm. It contains a large number of heteroatoms, such as N and O atoms, which can react with Pd 2+ Forming a strong coordination, not only has the 2+ It has good detection ability, strong adsorption ability, and high thermal stability. It has good anti-interference performance in the complex environment of actual detection. 2+ Adsorption capacity up to 1433.5 mg g -1 , which is higher than most other fluorescent porous organic polymers with detection effects that have been reported. In addition, the synthesis of this material is very simple and green, and it is superior to all other reported Pd in ​​terms of synthesis steps and synthesis time. 2+ Porous organic polymers with detection and adsorption capabilities. In addition, the polymer has good anti-interference in complex environments and produces easy-to-carry test strips for real-time online detection of Pd 2+ The fluorescent porous organic polymer prepared by the present invention is suitable for optical indication and recycling.

[0035] Compared with the prior art, the present invention has the following advantages:

[0036] 1) The prior art generally adds an amino monomer, an aldehyde monomer and an acid catalyst to the synthesis method. The acid catalyst causes the amino group in the amino monomer to be protonated, reduces the nucleophilicity of the amino group, and leads to low reaction efficiency. It usually requires an organic solvent environment, high temperature and a long reaction time. Different from the conventional two-step method that requires the synthesis of organic polymers first, the present invention adopts the strategy of pre-activating the aldehyde monomer with an acid catalyst to avoid the reduction of the nucleophilicity of the amino monomer, accelerates the generation of the semi-amine aldehyde intermediate, improves the efficiency of the reaction, and allows the Schiff base condensation to be rapidly synthesized in the aqueous phase at room temperature. This method uses common commercially available chemical raw materials as monomers, and a one-step reaction is used to prepare a fluorescent porous organic polymer. The material can be prepared in a very short time at room temperature without the need for an organic solvent, greatly simplifying the preparation process, reducing costs, and not requiring the use of precious metal catalysts. In addition, the synthesis process is green and environmentally friendly, does not cause environmental pressure, and is easier to achieve mass production, providing a good foundation for the application and promotion of fluorescent porous organic polymers.

[0037] 2) The fluorescent porous organic polymer of the method of the present invention uses 4,4-biphenyldicarboxaldehyde and 1,3,5-benzenetricarboxylic acid hydrazide as monomers, and the preparation of the porous polymer connected by hydrazone bonds is achieved through Schiff base reaction, thereby achieving its simple and green preparation process. In addition, the fluorescent porous organic polymer prepared by the method of the present invention has a large size and good dispersibility in water, which is conducive to recovery in water and optical indication.

[0038] 3) The prepared fluorescent porous organic polymer has a rod-like structure, a large specific surface area, good stability and anti-interference properties, and is suitable for fluorescent indication in complex environments.

[0039] 4) The prepared fluorescent porous organic polymer has a good affinity for Pd 2+ It has good adsorption performance and fluorescence indication. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention, but do not constitute a limitation of the present invention.

[0041] Figure 1 is the infrared spectrum of the reaction raw materials and products; TNO is 1,3,5-benzenetricarboxylic acid hydrazide, TM is 4,4'-biphenyldicarboxaldehyde;

[0042] Figure 2 is a scanning electron microscope image of the polymer;

[0043] Figure 3 is the XRD spectrum of the polymer;

[0044] Figure 4 It is the adsorption isotherm diagram and pore size distribution curve diagram of the polymer;

[0045] Figure 5 This is the thermogravimetric test diagram of the polymer;

[0046] Figure 6 Prepare the reaction equation for the present invention;

[0047] Figure 7 For polymer to Pd 2+ Langmuir adsorption isotherm model for adsorption;

[0048] Figure 8 For polymer to Pd 2+ Kinetic model of adsorption;

[0049] Fig. 9 Pd before and after adsorption 2+ Physical comparison of solution and polymer materials;

[0050] Fig.10For polymer to Pd 2+ Adsorption cycle diagram;

[0051] Fig.11 Comparison of fluorescence spectra of monomer and synthesized polymer under 365nm excitation;

[0052] Fig.12 The polymers were treated with different concentrations of Pd 2+ Fluorescence quenching diagram in interacting aqueous solution; the upper right corner is the visualization legend;

[0053] Fig.13 is the fluorescence intensity of the polymer to Pd 2+ Linear relationship with concentration.

[0054] Fig.14 For polymer to Pd 2+ Anti-interference of adsorption. DETAILED DESCRIPTION

[0055] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0056] The raw materials used in the present invention are all commercially available products, and all solutions are prepared using ultrapure water with a resistivity of 18.25 MΩ; the equipment used is also a commercially available product.

[0057] If no specific technology or conditions are specified in the embodiments of the present invention, they can be carried out according to the technology or conditions described in the literature in the field or according to the product manual.

[0058] Example 1

[0059] A method for preparing a palladium adsorbent with a fluorescent indication function, specifically comprising:

[0060] 63 mg of 4,4-biphenyldicarboxaldehyde was dispersed in a mixed solution of 5 mL of glacial acetic acid and deionized water in a volume ratio of 1:1, and ultrasonic treatment was performed for 30 min to obtain a 4,4-biphenyldicarboxaldehyde suspension; 50 mg of 1,3,5-benzenetricarboxylic acid hydrazide was dispersed in 5 mL of deionized water and ultrasonic treatment was performed for 30 min to obtain a 1,3,5-benzenetricarboxylic acid hydrazide suspension; the dispersed 1,3,5-benzenetricarboxylic acid hydrazide suspension was dripped into the 4,4-biphenyldicarboxylic acid suspension drop by drop with a dropper, and the reaction was carried out. The bottle was placed in an oil bath at 25°C for reaction for 10 minutes. 4,4-biphenyldicarboxaldehyde was activated by glacial acetic acid and reacted with 1,3,5-benzenetricarboxylic acid hydrazide to undergo Schiff base dehydration to generate a fluorescent porous organic polymer. The product was collected by filtration and washed with water and tetrahydrofuran for 5 times. The possible unreacted monomers were extracted with tetrahydrofuran for 24 hours. The product was dried in a vacuum drying oven at 60°C for 24 hours and stored at room temperature for later use. The obtained porous polymer was called TMTNO.

[0061] The following characterization and testing were performed on the materials:

[0062] 1. Infrared spectrum test

[0063] The prepared porous organic polymer was characterized by a Fourier transform infrared spectrophotometer with the brand INVENIOS. The test results are as follows Figure 1 .Depend on Figure 1 It can be seen that the Fourier transform infrared (FTIR) spectrum of the prepared fluorescent porous organic polymer relative to the monomer used shows that in the infrared spectrum of the synthetic polymer, at 2720 cm -1 The stretching vibration of -CHO disappears from the FT-IR spectrum, and the 1253 cm -1 The new C=N stretching vibration confirms the completion of the Schiff base reaction.

[0064] 2. Scanning Electron Microscope Characterization

[0065] The morphology of porous organic polymers was characterized by a Regulus 8100 scanning electron microscope. The test results are as follows: Figure 2 It was found that the prepared porous polymer was in the shape of a rod with a thickness of about 200 nm.

[0066] 3. X-ray diffraction detection

[0067] The porous organic polymer was characterized by a powder X-ray diffractometer of the brand SmartLab 9kw. The test results are as follows: Figure 3 .Depend on Figure 3 It is known to prepare porous organic polymers as amorphous solids.

[0068] 4. Surface area and pore size distribution by nitrogen adsorption and desorption

[0069] The surface area and pore size distribution of the polymer were determined by using a Micromeritics ASAP 2460 fully automatic specific surface and porosity analyzer using nitrogen adsorption and desorption at 77k and 1bar. Figure 4 The specific surface area of ​​the material is 48.3530m 2 / g, and the average pore size is 11.5728nm.

[0070] 5. Thermal stability analysis

[0071] The material was tested by thermogravimetric analysis using a Netzsch STA 449F5 thermogravimetric analyzer. Figure 5 As shown, the polymer is still stable at 337.3℃, and the results show that the polymer has good thermal stability.

[0072] 6. Adsorption test

[0073] In order to demonstrate that the synthesized fluorescent porous polymer is 2+ It has good adsorption capacity and adsorption experiments were carried out.

[0074] First, prepare Pd with concentrations of 100ppm, 200ppm, 300ppm, 400ppm, 500ppm, 1000ppm, 1500ppm, and 2000ppm. 2+ 5 mL of the solution was added, and 5 mg of the polymer sample prepared in Example 1 was added respectively. After 60 min, the sample was filtered for use. The obtained sample was tested under an inductively coupled plasma emission spectrometer with the brand name iCAP PRO X. The obtained data conformed to the Langmuir adsorption isotherm model, such as Figure 7 shown.

[0075] Prepare 1500ppm Pd 2+ 50 mL of ion solution was added, and 50 mg of the polymer powder prepared in Example 1 was added and stirred evenly. After 15 min, 30 min, 45 min, 60 min, 90 min, 120 min, 180 min, and 240 min, 3 mL of the aqueous dispersion was taken and filtered. The obtained samples were tested under an inductively coupled plasma emission spectrometer with the brand name iCAP PRO X. The obtained data were tested by the pseudo first- and second-order kinetic model prepared by the model. It was found that the material basically reached adsorption equilibrium at 90 min, and for Pd 2+ The removal rate is as high as 95.6%. The results are as follows Figure 8 As shown in the figure, the polymer is calculated based on the model to be 2+ The maximum adsorption capacity is 3061.38 mg g -1 .

[0076] Pd before adding polymer 2+ The solution was dark brown. After adding the polymer for 2 h, a clear solution was obtained by filtration. The polymer changed from light yellow to brown. Fig. 9 shown.

[0077] In order to prove the recycling ability of the polymer, the adsorbed material was eluted with thiourea solution and dilute nitric acid solution, and it can be reused after drying. It was ultrasonicated for 30 min in a mixed solution of 0.1 mol / L thiourea and dilute nitric acid (the mixed solution of thiourea and dilute nitric acid, the solvent is water, the concentration is 0.1 M) and the Pd 2+ The removal rate can still reach more than 90%. Fig.10 As shown, the polymer has good recycling ability.

[0078] 7. Fluorescence spectrum test

[0079] The fluorescence test of the monomers 1,3,5-benzenetricarboxylic acid hydrazide and 4,4-biphenyldicarboxaldehyde and the prepared porous polymer in Example 1 was performed by a fluorescence spectrometer of the brand Hitachi F-4700 under 365nm excitation. The results are as follows: Fig.11 The maximum fluorescence emission peak of the polymer undergoes an obvious red shift, indicating that the fluorescence peak of the polymer does not come from the monomer.

[0080] 8. Pd 2+ Optical indication experiment

[0081] The solid palladium nitrate dihydrate was mixed in water and then diluted to obtain different concentrations of Pd 2+ The solution was added to a polymer suspension of the same concentration (5 mg of polymer dispersed in 50 mL of water) and ultrasonicated for 30 min. 2+ The concentration gradients were 0 μM, 30 μM, 50 μM, 100 μM, 150 μM, 200 μM, 250 μM, 300 μM, 350 μM, and 400 μM. Then, 1 mL of each solution was transferred to a fluorescent tube with an optical path length of 1 cm using a pipette. Fluorescence testing was performed under 365 nm excitation using a fluorescence spectrometer of the brand Hitachi F-4700. The results are shown in Figure 2. Fig.12 and Fig.13 As shown, the fluorescence intensity is related to Pd 2+ There is a good linear relationship between the concentrations. The detection limit equation is 3σ / k, and the detection limit is 2.67μM.

[0082] IX. Adsorption selectivity experiment and anti-interference experiment

[0083] In 25mL containing Na + , K + Mg2+ 、Al 3+ 、Ni 2+ , Cu 2+ , Pd 2+ 5 mg of the polymer prepared in Example 1 was added to the solution with a concentration of 100 ppm. After two hours, the sample was filtered and tested on an iCAP PRO X inductively coupled plasma emission spectrometer. The results are as follows: Fig.14 , indicating that the polymer has a strong affinity for Pd 2+ Maintains good selectivity and anti-interference.

[0084] The inventors found that the use of acid catalysts is crucial for Schiff base condensation reaction and porous polymer formation. The Schiff base condensation reaction includes two steps: the first step is the nucleophilic attack of amine on aldehyde to form a half-amine aldehyde intermediate, and the second step is the dehydration of the half-amine aldehyde intermediate to generate a Schiff base compound. The acid catalyst plays different roles in the two steps of Schiff base condensation. In the first step, the presence of acid will protonate the amine, inhibit the nucleophilic attack of amine on aldehyde, and hinder the reaction. In the second step, an acid catalyst must be involved, and the acid protonates the half-amine aldehyde intermediate to form an -OH leaving group, which is further dehydrated to form a Schiff base. In the synthesis method of adding amino monomers, aldehyde monomers and acid catalysts at the same time, the acid catalyst causes the amino group in the amino monomer to be protonated, reduces the nucleophilicity of the amino group, and leads to low reaction efficiency, usually requiring an organic solvent environment, high temperature and a long reaction time. In the present invention, the strategy of pre-activating the aldehyde monomer with an acid catalyst is adopted to avoid the reduction of the nucleophilicity of the amino monomer, accelerate the generation of the half-amine aldehyde intermediate, improve the efficiency of the reaction, and enable the Schiff base condensation to be rapidly synthesized in the aqueous phase at room temperature. The two monomers used in the present invention, 1,3,5-benzenetricarboxylic acid hydrazide and 4,4-biphenyldicarboxaldehyde, have no other large-sized groups adjacent to the carbonyl and amino groups in the monomers, and have less steric hindrance in nucleophilic reactions, making it easier to synthesize polymers compared to other monomers. In addition, the hydrolysis resistance of the hydrazone bond (C=NNHR) Schiff base also improves the synthesis efficiency of porous polymer materials in aqueous solution. The hydrazone bond POPs synthesized by the present invention is an amorphous material with a low requirement for the bonding rate between monomers, so it can be quickly synthesized at low temperature and in aqueous solution.

[0085] The adsorption material prepared by the present invention is a porous polymer connected by a hydrazone bond (C=NNHR) Schiff base, and the lone pair of electrons in the adjacent N atoms can be delocalized into the C=N bond, the electronegativity is reduced, it is not easy to hydrolyze, and it has better chemical stability in water. In the porous polymer connected by the traditional imino group (-RC=N-) Schiff base, the nitrogen atom has a higher electronegativity than the carbon atom, and it is easy to undergo a hydrolysis reaction with water molecules. Therefore, compared with the imino group (-RC=N-) Schiff base, the hydrazone bond (C=NNHR) Schiff base has a higher aqueous phase synthesis efficiency and is more suitable for component enrichment and adsorption in aqueous solution. Compared with other reported materials, the synthesis of this material is very simple, and the preparation of the material can be completed in only 10 minutes at room temperature, and no organic solvent is required in the process. The entire reaction process is green and pollution-free, and has the potential for large-scale preparation. Compared with other reported palladium adsorbents, this material has an optical indication performance while having the ability to adsorb palladium, which can play an indicating effect on the palladium adsorption process to a certain extent. The material prepared by the invention is a porous polymer, which has the advantages of stable chemical properties and reusability.

[0086] The description of the above embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the protection scope of the present invention.

Claims

1. A method for preparing a palladium adsorbent with a fluorescent indication function, characterized in that: The preparation method is specifically: The aldehyde compound is dispersed in a mixed solution of acid and water, and a suspension of hydrazide compound and water is added dropwise to the obtained suspension of the aldehyde compound, and the mixture is stirred at room temperature to react, thereby obtaining a palladium adsorbent with a fluorescent indication function.

2. The preparation method according to claim 1, characterized in that: The molar ratio of the hydrazide compound to the aldehyde compound in the suspension of the hydrazide compound and water is 2:

3.

3. The preparation method according to claim 1 or 2, characterized in that: The concentration of the hydrazide compound in the suspension of the hydrazide compound and water is 0.03-0.05 mol / L.

4. The preparation method according to claim 1, characterized in that: The volume ratio of acid to water in the aldehyde compound suspension is 1:1-1.

5.

5. The preparation method according to claim 1 or 4, characterized in that: The dosage ratio of the aldehyde compound to the mixed solution of acid and water in the aldehyde compound suspension is 0.04-0.07 mol / L.

6. The preparation method according to claim 1, characterized in that: The acid is glacial acetic acid; the hydrazide compound is selected from 1,3,5-benzenetricarboxylic acid hydrazide; and the aldehyde compound is selected from 4,4-biphenyldicarboxaldehyde.

7. The preparation method according to claim 1, characterized in that: The room temperature stirring reaction refers to the reaction at 20-30°C for 5-20 minutes.

8. A palladium adsorbent with fluorescent indication function prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The palladium adsorbent with fluorescent indication function has the structural formula:

9. The palladium adsorbent with fluorescent indication function according to claim 8, characterized in that: The palladium adsorbent with fluorescent indication function is in the shape of a rod with a thickness of 150-250 nm. The specific surface area of ​​the palladium adsorbent with fluorescent indication function is 48.3530 m 2 / g, and the average pore size is 11.5728nm.

10. Use of the palladium adsorbent with fluorescent indication function according to claim 8 or 9, characterized in that Used for adsorption recovery of palladium or for monitoring adsorption recovery of palladium.

Citation Information

Cited By

  • Porous organic polymer as well as preparation method and application thereof

    CN122563044A